Study of Fly’s Behavior as a Parameter of The Impact of Toxic Compounds on Living Things - Zubaidah, Siti; Setiawan, Deny; Ramadhan, Muhamad Justitia; Zahrah, Natasya Adiba; Kharomah, Sinta; Hayuana, Wachidah; Fahmi, Muhammad Iqbal Najib; Fauzi, Ahmad (El-Hayah:Jurnal Biologi, 2024)
Various toxic compounds still often contaminate the environment and food of living things to this day. Drosophila is often used as a model organism to study the negative effects of exposure to toxic compounds on organisms. The purpose of this systematic literature review (SLR) is to analyze the distribution, contribution, and gap analysis of studies reporting the effect of toxic compounds on behavior in Drosophila. After conducting a search in the Scopus database, 57 titles that matched the entered search query were obtained. After selection and evaluation step, a total of 19 Scopus indexed articles that met the inclusion and exclusion criteria were successfully collected for analysis. The three countries that most frequently research Drosophila behavior are the US, China, and Nigeria. A total of 5 clusters resulted from the results of bibliometric analysis. Various behavioral studies have included developmental variables, gene expression, to the Circadian clock. Toxic compounds that are often studied generally come from the group of metal compounds. On the other hand, multigenerational studies to analyze the long-term effects of toxic compounds and the plasticity of phenotypic changes into gap analysis have been successfully identified.